Marketing analysis of some groups antidiabetic medicines, presented at pharmaceutical market of Ukraine - I. V. Vyshnytska; V. V. Trokhymchuk (The State Expert Center of the Ministry of Health of Ukraine, 2018)
The scarcity of state resources, the social economic and demographic situation, the deterioration of health status of population require new state approaches of organizing medical and pharmaceutical provision for the population. The aim of the study is the drug supply for patients with type ІІ diabetes. Relevance of theme is determined by the prevalence of the disease, the development of complex concomitant diseases, complications, early disability and high mortality due to low-quality and untimely medical and pharmaceutical care for this category of patients. The object of marketing research was the drugs registered in Ukraine, which cost is the subject to reimbursement for outpatient treatment of patients with type ІІ diabetes by the conditions of March 2017. The search for the proposals of drugs under study on the website of Morion Company was also conducted to assess the real state of the pharmaceutical market on this issue. The main used methods are bibliographic, statistical, marketing, graphic and systematization. The Ukrainian pharmaceutical market of drugs with the cost, which is the subject to reimbursement for outpatient treatment of patients with type II diabetes, has been investigated, and found that Gliclazide and Metformin are registered on the territory of Ukraine in the form of 22 and 91 medicines, respectively. The part of domestic producers of Gliclazide and Metformin is 36% and 33%, respectively. It was revealed, that the assortment of drugs Gliclazide and Metformin, which are available in the pharmacy network, is 2 and 1.4 times less than registered in Ukraine, respectively. Gliclazide and Metformin tablets are offered by domestic and foreign manufacturers in a dosage of 30 mg, 60 mg, 80 mg and 500 mg, 800 mg, 1 000 mg, respectively.